Imunização com anticorpo monoclonal anti-idiotípico de Bevacizumab 10.D7 causa alterações angiogênicas e interferência no crescimento de melanoma B16F10 - Sanches, Jessica de Souza [UNIFESP] (2016)
Melanoma is a highly aggressive form of skin cancer for which conventional therapies show low efficacy. It is known that vascular endothelial growth factor (VEGF) plays an important role in the angiogenic process of solid tumors and that the humanized monoclonal anti-VEGF antibody, bevacizumab, has been used in the treatment of some tumors. However, adverse effects such as bleeding and hypertension due administration of the antibody necessarily in high doses, can compromise their use. Based on the idiotypic network theory, our group has proposed to obtain bevacizumab anti-idiotypic (anti-Id) monoclonal antibodies (mAbs) that mimic VEGF for be used as an immunogen. The anti-Id mAb was obtained from Bevacizumab 10.07 and selected for study. C57BI/6 mice were then immunized with anti-Id mAb 10.07 ten days prior to implantation of B16F10 murine melanoma cells and tumor growth was monitored. The study showed that in the group immunized with anti-Id mAb, the tumors grew less than in the control groups. Tumors were analyzed for the presence of necrotic areas and angiogenesis. The results show that the tumors of animais immunized with 10.07 showed higher necrosis area and lower formed vessels and that the sera of these animais presented anti-anti-Id antibodies binding VEGF, which inhibited the formation in vitro tubes. Together, these results suggest that immunization with anti-Id mAb 10.07 impairs the development of B16F10 tumor.